Overall survival and role of programmed death ligand 1 expression in patients with metastatic non-small-cell lung cancer and immunotherapy: an observational study from central Switzerland - Valentina Allmann; Daniela Dyntar; Dirk Lehnick; Marco Dressler; Kristin Zeidler; Philipp Niederberger; Jeanne Godau; Joachim Diebold; Oliver Gautschi (Swiss Medical Weekly, 2023)
BACKGROUND: In clinical trials, therapy with immune checkpoint inhibitors has improved the survival of patients with metastatic non-small-cell lung cancer (NSCLC). These trials were important for drug approval and for defining new treatment standards but the effect of checkpoint inhibitors in patients treated outside of clinical trials is not well known. The goal of this study was to assess the effect of immunotherapy on the overall survival of patients with metastatic NSCLC in the region of central Switzerland.